Yard Crane Scheduling to Minimize Total Weighted Vessel Loading Time in Container Terminals - Huang, Shell Ying (2017)
One of the most important objectives for container terminals is to minimize the total weighted turnaround time for vessels. Minimizing total weighted vessel loading time directly helps minimize total weighted vessel turnaround time. In this paper we consider the yard crane (YC) scheduling problem in a multi-vessel loading process. We propose a YC scheduling system that minimizes the total weighted maximum tardiness of loading jobs. Our experiments show that this is significantly more effective in the minimization of the total weighted vessel loading time than the existing YC scheduling methods that minimize job waiting time or makespan. Our scheduling system also has the ability to dynamically optimize the YC operations with the consideration of the maximum tardiness already incurred to each vessel earlier in the loading process. To evaluate against our YC scheduling system, an optimal algorithm to minimize makespan (useful if there is YCs shortage) and an optimal algorithm to minimize total weighted job tardiness (common in manufacturing) are also proposed.